2010
DOI: 10.1590/s0104-77602010000300013
|View full text |Cite
|
Sign up to set email alerts
|

Ion input via rainwater in the southwestern region of Rio Grande do Sul, Brazil

Abstract: Ion input via rainfall alone and after interception by the forest canopy, constitutes an important path of biochemical cycling, although few studies have provided information on the subject so far. The objective of this work is to quantify ion inputs, via rainfall, in the southwestern region of Rio Grande do Sul state, Brazil. Ten rain gauges were mounted in a field area. The quantification of stored water volume, along with sample collection for determination of nitrate, nitrite, ammonium, phosphorus, sulfur,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
(12 reference statements)
0
5
0
1
Order By: Relevance
“…These results indicate the influence of precipitation volume on nutrient flow, since there is a lower quantity of ions contributed by wet atmospheric deposition in this study, when compared to Bellot & Escarre (1991), Calil et al (2010), andHeartsill-Scalley et al (2007).…”
Section: Nutrient Input Via Incident Rainfall Throughfall and Stemflowmentioning
confidence: 49%
“…These results indicate the influence of precipitation volume on nutrient flow, since there is a lower quantity of ions contributed by wet atmospheric deposition in this study, when compared to Bellot & Escarre (1991), Calil et al (2010), andHeartsill-Scalley et al (2007).…”
Section: Nutrient Input Via Incident Rainfall Throughfall and Stemflowmentioning
confidence: 49%
“…In 2004, only part of Europe had deposition higher than 10 kg ha -1 . These results are relevant to the reduction of particulate emissions by the best efficiency of the filters, therefore, for the study developed by Calil et al (2010), the quantities were above average.…”
Section: Concentration Of Ionsmentioning
confidence: 74%
“…Caggiano et al (2014) found an increase in K + levels in the Tf: 572 and 486% for Fagus sylvatica L. and Spruce abies L., relative to the incident precipitation. Calil et al (2010) studied the precipitation via nutrient inputs in the southeast of Rio Grande do Sul. The average rainfall of the two years evaluated was 1588 mm, about 12% higher than the historical average for the region.…”
Section: Concentration Of Ionsmentioning
confidence: 99%
“…Atmospheric particles composed of dust (Wu et al, 2013), soot released after vegetation burning (Laclau et al, 2003), volatilized nutrients from fertilization with limestone powder (Calil et al, 2010), and residues from liming in rural areas, are some of the sources of anions and cations to the atmosphere, which can affect the pH of rainwater and also increase the concentrations of NO 3 -, SO 4 2and Cl -. When these ions are present in rainwater they contribute to the nutrition of agricultural crops, native grasslands, pastures, and silviculture, which are widely cultivated in the Pampa biome.…”
Section: Resultsmentioning
confidence: 99%